Peregrinatio Religiosa - Michał Rożek (Folia Historica Cracoviensia, 1998)
Formally still the capital of the Republic of Poland, the coronation city and the royal necropolis, Krakow played an important part before the campaign of Vienna. It was in Krakow that the army concentrated, and it was to Krakow that John III Sobieski made his pilgrimage (peregrinatio religiosa) to patron saints of the nation, praying for a successful finale of the campaign against infidels. In Wawel he received his papal blessing. Several days before departing with his army, king John III had taken part in many religious celebrations to request special grace from the divine providence for himself, his son James and his army. This was the start of John III's peregrinatio religiosa, on a scale hitherto unprecedented in Polish religious culture.